Pengaruh Current Ratio, Debt To Equity Ratio, dan Net Profit Margin Terhadap Pertumbuhan Laba - Izzah, Nurul; Richmayati, Maya; Sandra, Elminaliya (Jurnal Liga Ilmu Serantau, 2024)
The aim of the research studied is to find out the influence of the current ratio, debt to equity ratio, and net profit margin on profit growth in food and beverage companies listed on the Indonesia Stock Exchange for the period 2018 to 2022. The method used in this research is called quantitative techniques. This research looked at 26 food and beverage companies that were listed on the Indonesia Stock Exchange, the research sample was found to be 11 companies, this sample was selected randomly using a method called purposive sampling, which takes into account a number of factors. Secondary data was collected from the Indonesia Stock Exchange website (www.idx.co.id) in the form of financial records of food and beverage companies from 2018 to 2022. Documentation studies and literature studies are the methods used to collect data. Multiple linear regression analysis was used to view the data in this quantitative research, and the SPSS Version 25 program was used to process the data. The research results show that the current ratio partially has no significant effect on profit growth. Conversely, the debt to equity ratio and net profit margin have a significant influence on profit growth. Meanwhile, the current ratio, debt to equity ratio, and net profit margin together have a significant effect on profit growth. R-Square data shows that the current ratio, debt to equity ratio, and net profit margin only have an influence of 29% on the dependent variable of profit growth. Meanwhile, the other 71% was caused by independent variables that were not related to the research being studied